Afatinib boosts CAR-T cell antitumor therapeutic efficacy via metabolism and fate reprogramming - Xi Zhang; Yue Liu; Yueyu Dai; Lingna An; Fangyuan Zhong; Shifeng Lou (Journal for ImmunoTherapy of Cancer)
Background Chimeric antigen receptor T (CAR-T) cell therapy has been shown remarkable efficacy in the treatment of hematological malignancies in recent years. However, a considerable proportion of patients would experience tumor recurrence and deterioration. Insufficient CAR-T cell persistence is the major reason for relapse. Multiple strategies to enhance the long-term antitumor effects of CAR-T cells have been explored and developed. In this study, we focused on tyrosine kinase inhibitors (TKIs), which have emerged immunomodulatory potential besides direct tumoricidal effects.Methods Here, we screened 50 approved TKIs drugs and identified that afatinib (AFA) markedly enhanced the expressing of CD62L and inhibited reactive oxygen species level in T cells. And the underlying mechanisms of AFA medicating T cells were explored by detecting signal transduction, and metabolism pattern. Furthermore, we co-cultured AFA with CAR-T cells during the preparation stage and multianalyses of differentiation characteristics, metabolic profiling, and RNA sequencing revealed that AFA induce comprehensive metabolism remodeling and fate reprogramming. Based on it, we finally identified the antitumor efficacy of AFA-pretreatment CAR-T compared with negative-control CAR-T.Results We identified that AFA blocked the T-cell receptor (TCR) and phosphoinositide 3-kinase-protein kinase B-mechanistic target of rapamycin signaling pathways, induced metabolic reprogramming and modulated T-cell differentiation. When combined with CAR-T cells, AFA inhibited the exhaustion and enhanced the persistence and cytotoxicity. Our results revealed that the pretreatment of AFA enables to boost CAR-T cells with strong antitumor cytotoxicity in leukemia mouse model.Conclusions Our study systematically demonstrated that AFA pretreatment effectively enhanced CAR-T cells antitumor performance, which presents a novel optimization strategy for potent and durable CAR-T cell therapy.